Effect of lurasidone treatment on chronic mild stress-induced behavioural deficits in male rats: The potential role for glucocorticoid receptor signalling. (April 2020) - Calabrese, Francesca; Brivio, Paola; Sbrini, Giulia; Gruca, Piotr; Lason, Magdalena; Litwa, Ewa; Niemczyk, Monika; Papp, Mariusz; Riva, Marco A
Background: Stress represents one of the main precipitating factors for psychiatric diseases, characterised by an altered function of glucocorticoid receptors (GR), known to play a role in mood and cognitive function. We investigated the ability of the antipsychotic lurasidone to modulate the involvement of genomic and non-genomic GR signalling in the behavioural alterations due to chronic stress exposure Methods: Male Wistar rats were exposed to seven weeks of chronic mild stress (CMS) and treated with lurasidone (3 mg/kg/day) starting from the second week of stress for more five weeks. Gene expression and protein analyses were conducted in dorsal hippocampus. Results: Seven weeks of CMS induced anhedonia and cognitive impairment, which were normalised by lurasidone. At molecular level, CMS rats showed an increase of GR protein levels by 60% ( p <0.001 vs. CTRL/VEH) in the membrane compartment, which was paralleled by an up-regulation of phosphoSINAPSYN Ia/b by 88% ( p <0.01 vs. CTRL/VEH) and of the mitochondrial marker Cox3 by 21% ( p <0.05 vs. CTRL/VEH). Moreover, while exposure to the novel object recognition test increased the nuclear translocation of GRs by 96% ( p <0.01 vs. CTRL/VEH/Naïve) and their transcriptional activity in non-stressed rats, such mechanisms were impaired in CMS rats. Interestingly, the genomic and non-genomic alterations of GR, induced by CMS, were normalised by lurasidone. Conclusion: Our results further support the role of glucocorticoid signalling in the dysfunction associated with stress exposure. We provide novel insights on the mechanism of lurasidone, suggesting its effectiveness on different domains associated with psychiatric disorders.